Rheological Properties of Aged Crude Hard Wood Pyrolysis Oil - Kaombe, Divina (Tanzania Journal of Engineering and Technology, 2021)
Upon storage of the pyrolysis oil, aging reactions may initiate phase separation and change of the rheological properties. These changes lead to unfavourable fuel characteristics in handling, transportation and applications. Efforts have been made for alleviation including methods on how to avoid these aging effects and development of equipment capable of handling aged pyrolysis liquids with unfavourable fuel characteristics. Therefore, the aim of this study was to explore the rheological properties of phase separated pyrolysis liquid fuel. Two batches of a well €“ stored poplar wood pyrolysis oils were used for the investigation; one batch was diluted with water to represent the oils undergoing severe phase separation (forced phase separation), and another batch was not diluted. Steady and dynamic rheological tests were conducted at various temperatures. Homogeneous (whole oil) and the bottom phases of pyrolysis oils were used. Results revealed that the whole oils of both diluted and undiluted oils exhibited low viscosity Newtonian behaviours at higher temperatures and high viscosity non-Newtonian behaviours at low temperatures. The bottom phases of both diluted and undiluted oils exhibited nonNewtonian behaviours with significant higher viscosity than the whole oils. The strain and frequency sweep dynamic tests showed existence of weak structures in the whole oils and strong network structures in the bottom phases. This study suggests that the handling, transportation and application of the pyrolysis oils undergoing phase separation are possible when the oils are treated with higher temperatures predominantly in turbulent state. Keywords: Pyrolysis oils, whole oils, bottom phases, bottom fractions, phase separation, oligomers.